Intervensi Eye Mask terhadap Kualitas Tidur pada Pasien Coronary Artery Disease - Habid Al Hasbi; Diana Irawati; Melati Fajarini; Sutanta Sutanta; Ady Tyawarman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of eye mask intervention on the sleep quality of coronary artery disease patients, which can be caused by many factors, including lighting, bedside monitor sound, the disease suffered, and nursing actions. This research method is quantitative with a quasi-experimental design with a control group pretest-posttest design. The research results showed that the p-value was 0.001 < 0.05, meaning there was a significant difference in the sleep quality of the intervention and control groups. In conclusion, eye masks are an easy intervention to implement and can significantly improve sleep quality in coronary artery disease patients treated in the Intensive Cardiac Care Unit. Keywords: Eye Mask, ICCU, Sleep Quality